Rural-Urban Migration Among Women Farmers: Science Education, Survey, and Implication for Food Crop Production in Cross River State, Nigeria - J. B. Effiong; C. F. Aya (Universitas Pendidikan Indonesia, 2022)
The main objectives of the study were to: identify the socio-economic characteristics of the respondents, assess factors influencing women's food production activities and identify measures for reducing rural-urban migration among women farmers in the study area. A sample size of 200 farmers was randomly selected for the study. Data were collected using a set of structured questionnaires and interview schedules. The result obtained showed that most of the farmers were between the ages of 51-60 years (50.0%). Farmers' levels of education were the non-formal level of education (45.0%), primary level of education (35.0%), and secondary level of education (15%). Farming was their major occupation (52.5%) and trading (40.0%). 8-10 household size was the highest which promotes labour within the family (40.0%), 11 and above (30.0%). Family labour was the main source of labour supply (75.0%), and exchange labour (22.5%). Factors influencing women's crop production activities were lack of fertile farmland, old age, active engagement in domestic activities, and high cost of farm inputs, which were 22.5, 17.5, 13.5, and 11.5%, respectively. The findings showed that mechanization can reduce migration among women farmers. The study recommended that government should mechanise agriculture, loans should be given to corporative farmers while land tenure system should be reviewed to favour farming which will also help to reduce rural-urban migration among women farmers in Cross River State, Nigeria.